Family care at early COPD: Is there any risk for caregivers’ mental well-being? - Figueiredo, Daniela (2014)
Evidence shows that caring for a family member with advanced chronic obstructive pulmonary disease (COPD) is a stressful experience, often associated with caregivers’ poor mental health. Much less is known about the psychological well-being of family caregivers of patients with early COPD.